2018
DOI: 10.1097/prs.0000000000004586
|View full text |Cite
|
Sign up to set email alerts
|

A Shift on the Horizon: A Systematic Review of Assessment Tools for Plastic Surgery Trainees

Abstract: A number of tools exist to assess a range of plastic surgery skills, in both clinical and simulated settings. There is a need to determine the transferability of simulated assessments to clinical practice, as most available tools are simulation-based. Although additional psychometric testing of current assessment tools is required, particularly in the nontechnical domain, this review provides a base on which to build assessment frameworks that will support plastic surgery's transition to competency-based medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…57,59 Finally, studies consistently identified the necessity of rigorously implementing WBA on a larger scale (i.e., across multiple specialties or institutions) to collect larger sets of data and study broader educational, clinical, and cost outcomes. 75,167–171…”
Section: Resultsmentioning
confidence: 99%
“…57,59 Finally, studies consistently identified the necessity of rigorously implementing WBA on a larger scale (i.e., across multiple specialties or institutions) to collect larger sets of data and study broader educational, clinical, and cost outcomes. 75,167–171…”
Section: Resultsmentioning
confidence: 99%
“…70 Numerous reviews discussed assessment tools used in plastic surgery of various skill sets calling for further research into their correlation to clinical practice and further development. 76,77…”
Section: Discussionmentioning
confidence: 99%
“…70 Numerous reviews discussed assessment tools used in plastic surgery of various skill sets calling for further research into their correlation to clinical practice and further development. 76,77 Generally, skill sets can be divided into technical (psychomotor), and nontechnical (cognitive and affective), and training on cognitive skills should precede or be combined with training 129e on psychomotor skills to accelerate their learning. 37,42,78,79 This accelerates technical skills acquisition by decreasing the learner's cognitive load and facilitating the cognitive phase of skill learning.…”
Section: Design and Developmentmentioning
confidence: 99%
“…14 McKinnon et al have reviewed the myriad of technical and nontechnical competency measurement tools specifically studied with plastic surgery residents. 15 At Johns Hopkins University, residents and faculty both rated residents on “operative entrustability” using a web-based tool completed after each surgery. Using these ratings, the CCC was able to significantly reduce the amount of time spent reviewing each resident.…”
Section: Responsibilitiesmentioning
confidence: 99%